America and American studies: from metaphor to catachresis - Bollobás, Enikő (AMERICANA E-journal of American Studies in Hungary, 2018)
The topic of this paper is the conceptualization of “America,” especially its tropological and epistemic aspects—in literature and in American studies alike. I claim that in American literature, “America” and “Americanness” have been typically conceptualized by two tropes: metaphor (for example, Thoreau’s “different drummer”) and catachresis (for example, Philip Roth’s Coleman Silk). I also claim that a comparable move can be observed in the epistemic changes that American studies has been informed by in the past decades. While “Old American studies” was framed by the modern episteme and as such by a metaphorical understanding of “America,” “New American studies” is framed by what we might call, after Michel Foucault, the postmodern episteme, and as such, by the conceptualization of “America” and “Americanness” as catachresis.